Um estudo preliminar sobre humanização hospitalar: dando voz à médicos de uma UTI pediatrica sobre suas vivências em um hospital humanizado - Goldenstein, Eduardo (2006)
From the end of the Second World War on, medicine started to develop clinically and surgically in a way hitherto unknown. Due to more accurate diagnoses, new therapeutic resources and the development of new drugs and technological procedures that allowed physicians to risk major surgeries, sicknesses simply became extinct or controlled and life could start earlier and end later. But all this technological development ended up causing two new problems and two new challenges: the increase of sicknesses without well-established physiopathological bases, such as psychosomatic anxieties and illnesses, and a kind of deconstruction of the humanistic face of medicine -- a deconstruction that came to be known as the dehumanization of medicine. Perhaps this dehumanization of medicine should be understood as a need to reformulate the humanistic bases of the same, adapting to current technological advances, which certainly have changed the training and the performance of the physician as he exercises his profession. The focus of our attention during this research was to go back to the previous matter: the double concept of dehumanization-humanization of medicine, especially in hospitals. Theoretical support for understanding these concepts will be presented in the introductory chapters. The objective of this research has been to analyze the experience of the clinical practice of ICU pediatricians in a humanized hospital. We, therefore, adopted a specific qualitative research methodology based on the phenomenological-existential approach of Heidegger, Boss and Buber. Interviews were made and analyzed with five ICU pediatricians that work in a humanized children s hospital The doctors accounts reveal different views on: how to deal with death, with anxiety and with guilt; the presence of mothers in the ICU and the effect on hospital routine and medical clinical practice; the recognition (or non-recognition) of the physician s work by the parents and ICU professionals; (positive or negative) aspects of the physical environment of the ICU and of working conditions. Starting from the data collected, a profile can be made of the clinical experiences of those interviewed, emphasizing the strategies used by them to deal with the difficulties and adversities generally present in ICUs. The analysis of these experiences has revealed the importance of listening to the physicians and including the voice of the doctor in the humanization process of medicine and hospitals. New research fronts, in which are heard the voice of other doctors, other professionals, the mothers and the children too, have shown themselves to be important